FACE LIFT USING SILHOUETTE SOFT THREADS - de Matteo Vaz, Debora; Rech Feldmann, Cristina (Health and Society, 2022)
Beauty and youth have always been a people’s desire. Cosmetic procedures can help a lot, but nowadays there is a demand for more natural and less invasive interventions to alleviate the effects of aging. Absorbable traction thread, especially Silhouette Soft®, have obtained very satisfactory and long- lasting results for the patients. In addition to repositioning the tissues of the face and neck, Silhouette Soft® suture promotes a great formation of collagen thanks to the PLLA and PLGA present in its composition, and a greater durability caused by the system of cones and knots that enhance traction, anchoring and its stability. Orofacial harmonization is showing the trend of associating varied treatments, in all layers of the face and in three dimensions, to obtain natural and excellent results.